2019
DOI: 10.21203/rs.2.13490/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community Based Essential Newborn Care Practices and Associated Factors among Women Who Gave Birth at Home in Last Twelve Months in Amaro Woreda, Southern Ethiopia, 2019

Abstract: Introduction:- Significant numbers of women are giving birth at home; in this case community based newborn care is a means of bringing life-saving care to mothers and newborns at the community level. However, practice is challenging within the Ethiopian health system. Objective:- The aim of this study was to assess prevalence of community based newborn care practices and its associated factors among women who gave birth at home in Amaro Woreda, southern Ethiopia, 2019. Methods:- Across-sectional study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 3 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…The result of the study indicates the odds of mothers that had birth preparedness were 7.8 times more likely to receive a good practice of immediate newborn care for their newborn neonate as compared with newborns whose mothers had not birth preparedness activity. This nding is supported by Amaro Woreda, Southern Ethiopia, in which those newborn who had mother that had birth preparedness were 3.5 times more likely to receive a good practice of immediate newborn care as compared with newborns whose mother had not birth preparedness activity (27).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The result of the study indicates the odds of mothers that had birth preparedness were 7.8 times more likely to receive a good practice of immediate newborn care for their newborn neonate as compared with newborns whose mothers had not birth preparedness activity. This nding is supported by Amaro Woreda, Southern Ethiopia, in which those newborn who had mother that had birth preparedness were 3.5 times more likely to receive a good practice of immediate newborn care as compared with newborns whose mother had not birth preparedness activity (27).…”
Section: Discussionmentioning
confidence: 81%
“…This study also revealed that the odds of mother that had good knowledge on essential newborn care component were 5 times more likely to receive a good practice of immediate newborn care for their newborn neonate as compared with mother had poor knowledge on the components of essential newborn care. This nding is consistent with the study done in Wolayta zone southern Ethiopia in which newborns who had mothers with a lack of knowledge on essential newborn care component was 2.7 times less likely to receive a good practice of immediate newborn care as compared with their counterparts(5) and another study done in Southern Ethiopia in which newborn who had a mother with lack of knowledge on essential newborn care component were 0.2 times less likely to receive a good practice of immediate newborn care as compared with their counterparts (27). But it contrasted with a qualitative evidence synthesis done in low-and middle-income countries which revealed that there is no relationship between maternal factors and immediate newborn care (28).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that having a good BPCR plan results in a good uptake of maternal newborn and child health (MNCH) services. 25 , 26 This could be because those women with a good BPCR plan are less likely to be exposed to delays in seeking, reaching, and accessing MNCH services and this may lead to good compliance with the CBENC service items. This result may have a policy effect as BPCR is one of the 12 basic WHO recommendations for increasing the use of skilled maternity care and minimizing serious obstetric and neonatal complications by the well-timed use of facility care.…”
Section: Discussionmentioning
confidence: 99%
“…All the 25 included studies used cross-sectional study design and reported in the English language. Out of the 25 articles that were eligible and included in this meta-analysis, eight studies were conducted in Southern Nation Nationalities and Peoples Region (SNNPR) [22,23,26,31,34,35,39,42], six studies conducted in Amhara region [20,32,33,36,38,43], five studies in Tigray regional state [21,25,29,30,37], two from Oromia region [28,41], two from Addis Ababa (capital city of Ethiopia) [19,27], and one study conducted in Benishangul Gumz regional state of Ethiopia [40], and one from Harari [24]. In the current systematic review and meta-analysis, a total of participants was involved 13,001 with a response rate ranged from 96.6 to 100%.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The sample size of studies ranged from a minimum of 186 women [43] to a maximum of 970 women in Amhara [33]. Twenty-one of the included studies reported on the practice of ENC [20,22,23,25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], and nine provided data on knowledge of ENC [19][20][21][22][23][24][25][26]43] (Table 1). From the 25 included studies, nine studies had a quality score of seven, eight studies had a quality score of eight, and the remaining eight had a quality score of nine.…”
Section: Study Characteristicsmentioning
confidence: 99%